Consumer behaviour and material living standards in a transition economy: Venice (ca. 1650-1800) - Mattia Viale (2018)
According to some scholars, during the eighteenth century there was a radical transformation in lifestyle and of the dynamics of purchase and demand for goods. This significant change in private consumption patterns, the so-called consumer revolution, was one of the fundamental premises for the subsequent economic and industrial development. Today, it is believed that most of the early modern economies underwent some kind of consumer revolution. However, the empirical evidence to support this theory is almost exclusively based on the rich and advanced economies from the North-Atlantic areas. Few quantitative studies exist that address material living standards through changes in consumption patterns in European regions that only experienced industrial and economic development later. Therefore, numerous questions about these regions remain unanswered. What were the variations in the acquisition and consumption strategies in these areas? Was the process similar to that found in Northern Europe? What elements of a consumer society can be identified in these regions? This study aims to fill this gap in knowledge by analysing the material well-being of one of the most important and populous centres of Southern Europe: Venice between the seventeenth and eighteenth centuries. This research uses a wide body of empirical evidence, mainly unpublished documentation maintained at the Venetian State Archive. The principal source of this research is the household budgets preserved in the archive of the Giudici di Petizion judiciary. The results reveal how behind the apparent rigidity in consumption that we can trace, there were an extreme variety of consumer practices, already present in the Serenissima since the seventeenth century. Venetian consumer society appears, in fact, to have been especially articulated, faceted and segmented, and every actor behaved according to his or her unique set of preferences and desires. Therefore, we show how the logics of consumption do not respond to the logics of subsistence that for a ...